Multi-Objective Optimization Of Sustainable Building Designs For Energy Consumption Using Ai -Ml Framework - Chandra Shah, Mahesh (International Journal of Psychosocial Rehabilitation, 2019)
Sustainable building design plays a crucial role in reducing energy consumption and promoting environmental conservation. In this context, multi-objective optimization techniques combined with artificial intelligence (AI) and machine learning (ML) frameworks have emerged as powerful tools to enhance energy efficiency in buildings. This paper presents a comprehensive study on the application of AI-ML frameworks for multi-objective optimization of sustainable building designs, specifically focusing on energy consumption. The proposed framework leverages the capabilities of AI and ML algorithms to generate optimal solutions by simultaneously considering multiple conflicting objectives, such as minimizing energy consumption, maximizing occupant comfort, and reducing greenhouse gas emissions. The framework integrates various components, including data acquisition, pre-processing, feature extraction, model training, optimization algorithms, and performance evaluation. Through the application of AI-ML techniques, the framework utilizes historical building energy consumption data, weather patterns, building characteristics, and occupant behaviour to train predictive models. These models are then employed to simulate and evaluate different design scenarios, generating a set of Pareto-optimal solutions. The Pareto front represents the trade-offs between energy efficiency and other design criteria, enabling decision-makers to select the most appropriate sustainable building designs. The advantages of the AI-ML framework for multi-objective optimization of sustainable building designs are manifold. It enables rapid exploration of a wide range of design alternatives, improving decisionmaking efficiency and flexibility. Moreover, it facilitates the incorporation of dynamic factors such as weather patterns and occupant behaviour, enhancing the accuracy and adaptability of the optimization process. To validate the effectiveness of the proposed framework, several case studies are conducted using real-world building data. The results demonstrate that the AI-ML framework outperforms traditional optimization methods in terms of energy efficiency, occupant comfort, and environmental impact. Furthermore, sensitivity analyses are performed to investigate the robustness and generalizability of the framework under different scenarios. The integration of AI and ML techniques in multi-objective optimization frameworks for sustainable building design provides a powerful approach to improve energy efficiency and promote environmentally conscious construction practices. This research contributes to the advancement of intelligent building design processes, enabling stakeholders to make informed decisions that balance energy consumption, occupant comfort, and environmental sustainability. The findings of this study have significant implications for architects, engineers, policymakers, and researchers involved in the design and construction of sustainable buildings.